FLAVONOID CONTENTS AND 2,2-DIPHENYL-1-PICRYLHYDRAZYL RADICAL SCAVENGING ACTIVITY OF SOME EDIBLE MUSHROOMS FROM TURKEY: A. BISPORUS AND PLEUROTUS SPP. - Akyuz, Mehmet; Onganer, Ayse Nilay; Erecevit, Pinar; Kirbag, Sevda (New Century Health Publishers, Llc, 2012)
In this study, flavonoid and resveratrol contents and 2,2-diphenyl-1- picrylhydrazyl (DPPH) five radical scavenging activities of Agaricus bisporus, Pleurotus eryngii var. eryngii, P. eryngii var. ferulae, P. sajor-caju, P. ostreatus and Pleurotus sp. florida were determined. In addition, the amounts of resveratrol and flavonoid such as rutin, myricetin, morin, quercetin, kaempferol, catechin, naringenin were also determined to be 0.00-0.75 and 0.00-3.00, 0.00-11.75, 0.00-64.50, 0.00-0.50, 0.00-0.25, 0.00-39600, 0.00-2.00, mu g/g of dry weight, respectively. Furthermore, naringin was not detected in any of the samples. EC50 value in scavenging ability on DPPH free radical was 11.78% in P. ostreatus, 13.01% in P. sajor-caju, 13.11% in P. eryngii var. eryngii, 14.58% in Pleurotus sp. florida, 17.25% in A. bisporus and 24.67% in P. eryngii var. ferulae. In fact, P. streams was the most efficient species concerning antioxidant activity, while P. eryngii var. ferulae presented lower antioxidant properties. Based on EC50 values, P. ostreatus was good in antioxidant properties for the scavenging ability on DPPI free radical.
Keywords: A. bisporus; Antioxidant Activity; Edible Mushroom; Flavonoid Content; Pleurotus spp.